Optimization of energy efficiency and purge strategy of an open-cathode PEMFC stack with a dead-end anode configuration - Tan-Thich Do; Trung-Kien Vi; Phuoc-Dong Doan (International Journal of Renewable Energy Development, 2026)
Nowadays, proton exchange membrane fuel cells (PEMFCs) are acknowledged as promising energy solutions toward reaching net-zero emissions by 2050 due to their highlighted properties, such as high energy efficiency, high power density, low operating temperature, fast start-up, and zero emissions. To enhance electrochemical reactions and improve hydrogen utilization, the dead-end anode (DEA) configuration was employed to investigate the voltage and energy efficiency of an open-cathode PEMFC stack (100 W-20 cells) at optimal fan speed under varying purge intervals and operating current load levels with the step-by-step method. The hydrogen purge operation optimization was proposed by fitting experimental data and deriving the governing equation, considering voltage stability and hydrogen consumption. The results show that when the operating current and purge interval increased, the stack voltage decreased owing to impurities, water, and nitrogen buildup in the flow field anode channel. At optimal purge intervals of 540, 360, 280, and 60 s, the energy efficiency was achieved at 45.55%, 45.31%, 43.11%, and 35.05%, respectively. Compared to a previous study, these values represent increases of 25.22%, 12.91%, 9.15%, and 2.09% for operating currents of 1, 3, 5, and 8 A, respectively. These improvements were achieved by optimizing the fan speed, purge interval, and microcontroller unit power consumption. At a low load level of 1 A, the voltage decay rate decreased from 0.45 mV s−1 to 0.07 mV s−1, allowing for stable cell performance and higher hydrogen utilization at longer purging intervals. However, at higher load levels, both the voltage change of the stack and the voltage decay rate of the stack increased significantly compared to the 1 A case, with a steeper slope corresponding to higher current levels. This indicated that at higher reaction rates, the amount of water generated from the oxygen reduction reaction increases significantly. Consequently, the back diffusion phenomenon from the cathode to the anode, along with nitrogen buildup, leads to adverse conditions such as anode channel flooding and fuel starvation. This study provides meaningful insights into optimizing the energy efficiency of open-cathode PEMFC stacks across various load levels and purge operations.